Field evaluation of Bt 127SC formulation for efficacy against lepidopteran larvae infesting soybean under Manipur conditions: Field evaluation of Bt 127SC formulation for efficacy against lepidopteran larvae infesting soybean under Manipur conditions - NILIMA KARAM; H NANITA DEVI; T SUNANDA DEVI; L SOPHIA DEVI (Journal of Oilseeds Research, 2020)
Bt 127SC formulation supplied by the ICAR-Indian Institute of Oilseeds Research, Hyderabad was field tested at Imphal (Manipur) during kharif 2016-2018 against lepidopteran larvae infesting soybean. Two spray application of Bt 127 SC formulation @ 3 ml/litre of water was observed to be less superior to commercial synthetic insecticides but at par with Bt commercial Delfin in reducing Bihar hairy caterpillar and bean leaf webber and comparatively similar in efficacy with the synthetic insecticides in reducing tobacco caterpillar.